ROS-mediated lipopolysaccharide-induced apoptosis in INS-1 cells by modulation of Bcl-2 and Bax - Du, S-C.; Ge, Q-M.; Lin, N.; Dong, Y.; Su, Q. (Cellular and Molecular Biology, 2012)
Overproduction of reactive oxygen species (ROS) or exhaustion of antioxidants may cause oxidative stress which is a major factor of defective insulin secretion and increases apoptosis of pancreatic Î²-cells in diabetes. So there comes a consideration of whether antioxidant strategies can be used to protect deterioration of the Î²-cells. In this study, we explored the mechanism of oxidative stress mediated lipopolysaccharide (LPS) induced apoptosis in insulin secreting (INS-1) cells from a rat pancreatic Î²-cell line. ROS was monitored by using intracellular ROS capture dihydroethidium (DHE) and dihydrorhodamine123 (DHR123). Apoptosis rate was measured by flow cytometry (FCM). The pro-apoptotic gene Bax and anti-apoptotic gene Bcl-2 were analysed by Western blot and RT-PCR. The results demonstrate that LPS-stimulated INS-1cells manifest intensified intracellular fluorescence in both dose- and time- dependent manners. Apoptosis rate of LPSstimulated INS-1cells is significantly increased by FCM, with a significant increase in Bax/Bcl-2 ratio revealed by Western blot and RT-PCR. Furthermore, Î±-lipoic acid (Î±-LA) inhibits LPS-induced apoptosis, but can not restore the function of glucose stimulated insulin secretion (GSIS) in INS-1 cells.